Unresolved issues of increasing physical activity after myocardial infarction - D. Yu. Sedykh; O. N. Khryachkova; K. E. Krivoshapova; D. P. Tsygankova (Российский кардиологический журнал)
The review presents the results of studies on the problems of increasing the efficiency of rational  physical  activity  within the concept of comprehensive secondary  prevention of myocardial  infarction. The aspects of insufficient adherence of specialists and patients to rehabilitation methods were discussed; possible safe exercise modes after infarction and available monitoring methods were given. We also described the potential characteristics of physical training, taking into account the initial clinical severity  and completeness of revascularization after myocardial infarction. In addition, the need for socio-economic,  as well as informational support of the state and healthcare system has been updated.